PENERAPAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY DI KOTA DENPASAR - Ary Wulandari, Ni Putu; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
E-Filing is one of the outcomes of taxation system modernization, issued by Directorate General of Taxes in order to facilitatetax administration in Indonesia. However, it is necessary for taxpayers to conduct adjustment in applying the new system. This research aims to ascertain the factors affecting the interest in using e-Filing by applying Unified Theory of Acceptance and Use of Technology (UTAUT). UTAUT model used in this study consists of 4 factors, in which performance expectations, business expectations, social factors and conditions that facilitate are used as independent variables, and the interest on utilizing e-Filing as dependent variable. This research is conducted in Denpasar, using accidental samplingas sampling technique. Data were collected by distributing questionnaires to taxpayers who use e-Filingand analysed with multiple linear regression analysis.The results showed that performance expectation, business expectation, social factors, and conditions that facilitate affected the interest in using e-Filing positively and significantly.
Keywords: Unified Theory of Acceptance and Use of TechnologyModel, Performance Expectation, Effort Expectation, Social Factors, E-Filing